Influence of process-induced microstructure and additives (CO, AL, TI, C) on magnetic properties of ND-FE-B based isotropic hard magnetic materials - Sabbaghizadeh, Rahim (2015)
Nanocrystalline permanent magnets offer original magnetic features as a result of surface or interface consequences which are different from properties of bulk or microcrystalline materials. The main reason for this is the grain size and the presence or absence of intergranular stages. Most of the NdFeB research literature has only very superficially dealt with the question of how to improve the magnetic properties of the NdFeB materials. The literature has covered in great detail the answers for the case of Rare Earth-Iron-Boron-based materials obtained from high amounts of rare earth material. Thus, this work was a fresh attempt to critically track the influence of process-induced microstructure, additives and annealing temperature on magnetic properties of (Nd, Pr)-(Fe, Ti, C, Co, Al)-B isotropic nanocomposite alloys with unique compositions, containing medium amounts of boron and lesser amounts of rare earth material. Various routes were used to organize them, such as direct quenching with different roll rates, devitrification of amorphous over-quenched ribbons by annealing at different temperature ranges and mechanical alloying technique. The results of a methodical analysis of the relationship between microstructure and magnetic properties in isotropic nanocrystalline (Nd,Pr)-(Fe,Ti,C,Co,Al)-B permanent magnets were provided in the present study. The first section explains how microstructure and magnetic properties of (Nd,Pr)-(Fe,Ti,C)-B Melt-spun ribbons are dependent on the solidification rate (quenching wheel speed). Based on these results, the lower speeds were shown to increase the magnetic properties. Thus, we can develop a uniform Nd2Fe14B/Fe3B nanocomposite structure with fine soft grains at an optimum 5m/s quenching wheel speed. Moreover, it was shown that increasing quenching wheel speed results in reduced grain size and higher amount of amorphous phase. The second section, presents the impact of Titanium, Carbon, Cobalt and Aluminum additions on the crystallization behavior, microstructure and magnetic properties of (Nd,Pr)-Fe-B alloys with different compositions. It was shown that additions of Ti and C improved the glass forming ability and raised the temperature of crystallization. Ti addition led to considerable refinement of grain size as a result of the formation of amorphous grain boundaries enriched with Ti. Further C addition led to the enhancement of Ti enrichment in the grain boundary stage that increased coercivity and maximum energy product. The best magnetic properties were obtained from the samples which contain 3 atomic percentages of Titanium and Cobalt. In addition, it was shown that additions of Co increase the temperature of crystallization. Additionally, substitution of Co enhances the generation of 2:14:1 phase that leads to a considerable increase in coercivity of the ribbons. The appropriate substitution of Co makes intergranular exchange coupling of the grains stronger and results in the improvement of the remanence and energy product for the (Nd,Pr)2(Fe,Ti,C)14B/Fe3B type ribbons. The best magnetic properties were achieved for ribbons with Co3. Nevertheless, small aluminum addition improves coercivity. The Al and Co combination leads to Nd3Co and Nd(Fe,Al)2 formation at the grain triple points after heating and results in better magnetic isolation of grains. Also, the uniform grain boundary distribution and increasing anisotropy field of the alloys improve alloy coercivity. The third section investigates the effects of different annealing temperatures on the magnetic properties and structure of Nd-Fe-B nanocomposite permanent magnetic alloys with different compositions. Generally, it has been shown that the amorphous alloys’ crystallization behavior is strongly dependent on the temperature of heat treatment and the size and volume fraction of α-Fe and Nd2Fe14B can be manipulated by subsequent thermal processing. Furthermore, magnetic properties are highly dependent on the grain size of the hard and soft magnetic phase. Hence, the increase and decrease of annealing temperature will increase and decrease the magnetic properties. Finally, the best magnetic properties in type (E) and type (F) were achieved at 720 oC and 700 oC annealing temperatures respectively, with the (BH)max=60.48 KJ/m3 in type (F) ribbons.